The Impact of the Use of Sodo and Tiger Trawling Gear on Communities in Tambakrejo Fishers' Village, Semarang - Susilowati, Indah; Suciati, Ika; Kusumawardhani, Hapsari Ayu; Sari, Dwi Putri Wulan; Puspita, Sintia Diah (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
Based on the Regulation of the Minister of Maritime Affairs and Fisheries Number 2/PERMEN-KP/2015, sodo and trawlers are fishing gear prohibited from being used, especially by small fishers, because they are not environmentally friendly. However, many fishers still use this tool, one of whom is a fisherman who looks for fish in the waters of Tambakrejo, Semarang, which significantly disrupts the activities of Tambakrejo fishers. This study aims to identify the socio-demographic profile of Tambakrejo fishers, analyze the impact of using sodo and trawlers in Tambakrejo waters, and analyze strategies for handling the effect. This study uses primary data from semi-structured and in-depth interviews. The number of respondents in the study was 60, as determined by the purposive sampling method. This study uses a mixed-methods approach. Quantitative analysis in the form of descriptive analysis is needed to answer the first and second goals. At the same time, quantitative analysis is used to answer the third objective with the help of the Atlas.Ti tool. This study's results show that most fishers use traps and bamboo clumps. The dominating use of sodo and trawlers in Tambakrejo waters has an economic aspect in the form of reduced catches and damage to traps and clusters, as well as social aspects, namely the conflict between Tambakrejo fishers and fishers who use sodo and trawl nets. To deal with this impact, government intervention is needed in the form of water police patrols and strict action against fishers who use sod and trawl fishing gear. The results of this study are expected to be considered in formulating policies, especially fisheries policiesKeywords: Impact, trawlers, sodo, fishers, Tambakrejo